4D printing of thermal responsive structure for environmentally adaptive radiative cooling and heating. Issue 2 (4th November 2021) - Liu, Yuchen; Liu, Ruochen; Qiu, Jingjing; Wang, Shiren
Abstract: Four‐dimensional (4D) printing, which combines a three‐dimensional (3D) printing process with dynamic modulation of materials, provides a possible solution to achieve stimuli‐responsive microstructure that exhibit more complex functionality. One of the potential applications for these stimuli‐responsive hydrogels is switchable passive radiative cooling and warming. However, most current attempts are limited to mono‐functionality, either radiative cooling or warming only. In this article, we demonstrate a double‐side morphing flower structure for a dual functionality, switchable cooling or warming dependent on the environment. The morphing structure was designed with the aid of emissivity calculations and then fabricated by the 3D printing method. The transition between open‐flower and close‐flower states occurs at 32°C within a minute, resulting in 35% emissivity difference between these two states. As a result, the power difference between inner layer and outer layer was as high as 22 W/m 2 which is a function of pyramid bottom size. Abstract : Four‐dimensional (4D) printing was implemented to create stimuli‐responsive microstructure that can demonstrate switchable passive radiative cooling and heating.